The Influence of Using Gadgets as Learning Media on Writing Skills for Observation Report Texts - Seylla Mar'atus Solikhah; Sujarwoko; Andri Pitoyo (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to examine the difference in the skills of writing observation report texts between those who donot use gadgets as learning tools and those who use gadgets as a learning medium, as well as to determine the effect of using as a learning medium. The research was conducted at SMAN 1 Mojo during the 2025/2026 learning period. The population consists of 391 students of SMAN 1 Mojo in grade X. A randomization process was carried out to determine the sample that would represent each of the two classes. A control group of 36 students from class X-1 and 35 students from X-7 were obtained as the experimental group. The Pretest-posttest group design is used as a research design. Two writing tests are conducted, including before and after treatment, as a process of data collection. Then the data is processed to test for normality and homogeneity as well as the t-test. The findings revealed a disparity in writing skill achievements between those not using gadgets and those using gadgets. The group not using gadgets scored 65,69 and 71,81 respectively, while the group using gadgets scored 66,00 dan 81,14. The results of hypothesis testing indicate that the use of gadgets has a positive effect on the students writing skills who utilize gadget media in the process of learning to compile observation report results. The finding is proven by result of 4,441 exceeding the t distribution in the table of 1,995 with a 5% significance level.